Synthesis of 4-((1H-benzo[d]imidazol-2-yl)oxy)-3-methylpicolinic acid, a key related substance of Rabeprazole sodium. Issue 30 (23rd July 2020) - He, Xiaoyan; Chang, Yan; Bao, Xuefei; Liu, Zi'ao; Chen, Guoliang; Lu, Xiuhong
Graphical abstract: Highlights: Title compound is important in the process control of Rabeprazole sodium API. The synthetic route of title compound is rarely reported. This method provides an economic, environment friendly, and easy-to-operate way. Synthesis of 4-hydroxy-3-methyl-picolinonitrile was reported for the first time. Abstract: 4-((1 H -benzo[ d ]imidazol-2-yl)oxy)-3-methylpicolinic acid (11) is a key related substance of Rabeprazole sodium. In this article, this key related substance is synthesized by using 3-methylpicolinonitrile as a starting material via a five-step processes. By converting 3-methylpicolinonitrile to 4-hydroxy-3-methylpicolinonitrile (13), the preparation of TM becomes practical. This work provides a guarantee for quality standard establishment of Rabeprazole sodium.